Gait festination in parkinsonism: introduction of two phenotypes - Nonnekes, Jorik (J Neurol, 2018)
Gait festination is one of the most characteristic gait disturbances in patients with Parkinson’s disease or atypical parkinsonism. Although festination is common and disabling, it has received little attention in the literature, and different definitions exist. Here, we argue that there are actually two phenotypes of festination. The first phenotype entails a primary locomotion disturbance, due to the so-called sequence effect: a progressive shortening of step length, accompanied by a compensatory increase in cadence. This phenotype strongly relates to freezing of gait with alternating trembling of the leg. The second phenotype results from a postural control problem (forward leaning of the trunk) combined with a balance control deficit (inappropriately small balance-correcting steps). In this viewpoint, we elaborate on the possible pathophysiological substrate of these two phenotypes of festination and discuss their management in daily clinical practice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00415-018-9146-7) contains supplementary material, which is available to authorized users.